Attitudes, Knowledge, and Practices Regarding Chronic Kidney Disease Among Patients - Khan, Asma Samandar; Mukhtar, Hira; Haider, Shahbaz; Tesneem, Syeda Sidra; Jabeen, Rubina (Biological and Clinical Sciences Research Journal, 2025)
Chronic kidney disease (CKD) poses a growing public health burden globally, particularly in low- and middle-income countries like Pakistan. Patient knowledge, attitudes, and practices (KAP) are key factors influencing disease management and outcomes. Objective: To assess the knowledge, attitudes, and practices regarding CKD among patients receiving care in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted at Sheikh Zayed Hospital, Lahore. A sample of 180 CKD patients was recruited using convenience sampling. Data were collected using a structured, validated questionnaire covering demographic characteristics, knowledge, attitudes, practices, and risk factor awareness. Statistical analysis was conducted using SPSS version 25. Reliability was assessed via Cronbach’s alpha, and validity was evaluated using KMO and Bartlett’s tests. Results: The majority of participants were male (59.4%) and aged between 26–45 years. High levels of knowledge were observed regarding the progressive nature of CKD and the roles of hypertension and diabetes as risk factors. Attitudes were generally favorable, particularly regarding the importance of awareness and equal treatment. Practices such as medication adherence and blood pressure monitoring were common, but exercise and dietary compliance were low. Awareness of less common CKD risk factors such as aging, autoimmune disease, and NSAID use was limited. Cronbach’s alpha values ranged from 0.295 to 0.732 across domains, and KMO values confirmed construct validity. Conclusion: The study highlights moderate to high knowledge and positive attitudes toward CKD among patients, but also reveals gaps in practice and awareness of lesser-known risk factors. Targeted educational interventions are needed to promote comprehensive disease understanding and self-care behaviors.